Investigation of Anti-Inflammatory Potentials of Terminalia Tomentosa Wight & Arn. Bark - An In-Vitro Approach - Richard Lobo (Journal of Global Pharma Technology, 2017)
Terminalia tomentosa bark. Belongs to the family Combretaceae. Bark is astringent and useful in the treatment of ulcers, vata, fractures, hemorrhages, bronchitis and diarrhea.This study establish the anti-inflammatory activity of ethanolic (TEA) and aqueous (TEW) of T. tormentors aback extracts in in-vitro methods by Inhibition protein denaturation (BSA),Inhibition of Egg Albumin denaturationand The human HRBC membrane stabilization method., alcoholic and aqueous extracts exhibited significant protein denaturation inhibition in egg albumin assay with IC50 values TEA113µg/mL, TEW 112.67µg/mL in comparison with Standard (Diclofenac sodium) 236.7µg/ml. In bovine serum albumin denaturation assay with IC50 values TEA 16.91µg/mL and TEW 17.67µg/mL respectively when compared with standard (Diclofenac sodium) 67.21µg/mL. Both alcoholic and aqueous extracts were shown to have membrane stabilization properties with the IC50 values TEA 92.95µg/mL, TEW 37.68µg/mL respectively, in comparison with standard (Diclofenac sodium) 47.48µg/mLTo conclude, this study shows that the T. tormentors, possess significant anti-inflammatory activity.Keywords: Terminalia tomentosa, Anti-inflammatory, Combretaceae, HRBC, Egg albumin Protein denaturation.